Enhancing Health Education Using Edutainment: A Quantitative Study in Malang Regency, Indonesia - Muthmainnah Muthmainnah; Lutfi Agus Salim; Ira Nurmala; Asma Nadia; Annisa Clara Salsabila (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2025)
Introduction: Adolescent health education is essential for promoting long-term well-being, yet many students lack access to effective and engaging learning approaches. This study evaluates the impact of structured teacher training combined with edutainment-based interventions on improving adolescent health knowledge and behavioral intentions using the Theory of Planned Behavior (TPB) in Malang Regency, Indonesia. Methods: A quantitative pre-experimental design was used with a pre-test–intervention–post-test structure. The study involved 22 teachers from five schools and 56 junior high school students from SMPN 1 Kepanjen, Malang. The intervention included comprehensive teacher training and interactive edutainment sessions for students, covering topics such as adolescent characteristics, physical activity, assertive communication, and time management. Knowledge changes were analyzed using the Wilcoxon signed-rank test. Results: The intervention significantly increased knowledge in both groups. Students' average scores improved from 73.2 (pre-test) to 84.4 (post-test) (p < 0.001), while teachers’ scores increased from 69 to 83.4 (p < 0.001). However, no significant changes were observed in students' subjective norms, behavioral control, or behavioral intentions. Conclusion: Combining structured teacher training with edutainment is an effective strategy for enhancing adolescent health knowledge. This approach provides a scalable model for improving health literacy, though further efforts are needed to influence behavioral intentions and self-efficacy.